AB0003 Relationship Between Vegfa Gene Polymorphisms and Serum Vegf Protein Levels in Patients with Rheumatoid Arthritis. (9th June 2015) - Paradowska-Gorycka, A.; Pawlik, A.; Malinowski, D.; Romanowska-Prochnicka, K.; Haladyj, E.; Manczak, M.; Olesinska, M.
Abstract : Background: Rheumatoid arthritis (RA) is one of the chronic autoimmune diseases, with genetic and environmental predisposition, and synovial angiogenesis is considered to be a notable stage in its pathogenesis. Angiogenesis or vascular proliferation has been suggested to be a pivotal mechanism involved both inflammation/immune activation and joint invasion and destruction. RA may be considered an … angiogenic| disease" because it is associated with active tissue neovascularization. Vascular endothelial growth factor A (VEGFA) promotes vascular permeability, regulates angiogenesis, endothelial cell proliferation and migration, chemotaxis, and capillary hyper permeability and therefore is involved in the development of inflammation. VEGFA is the most potent proangiogenic molecule promoting the angiogenic phenotype of RA and is upregulated in RA. Objectives: The aim of the study was to identify functional VEGFA variants and their possible association with VEGF expression, susceptibility to and severity of RA. Methods: 581 RA patients and of 341 healthy individuals were examined for -1154 A/G, -2578 A/C VEGFA gene polymorphisms by PCR-RFLP method and for -634 G/C VEGFA gene polymorphisms by TaqMan SNP genotyping assay. Serum VEGF levels in RA patients and controls were measured by ELISA. Results: The -1154 A/G VEGFA gene polymorphism under the codominant, recessive (AA+AG vs GG) and dominant (AA vs AG+GG) models were associated with RA (p=0.0009; p=0.004; p=0.017, respectively). VEGFA -2578 A/C revealed differences in the case-control distribution in codominant, recessive, dominant and overdominant models (all p<0.0001). Furthermore, the -634 G/C VEGF gene SNP were not correlated with susceptibility to RA in Polish population. The genotype-phenotype analysis showed significant association between the VEGFA -1154 A/G and -634 G/A and mean value of the hemoglobin (all p=0.05), additionally they relevated that the number of women with the polymorphic allele -2578 C was lower than the number of women with wild type allele -2578A (p=0.006). Serum VEGF levels were significantly higher in RA patients than in control groups (both p=0, 0001). Conclusions: Present findings indicated that VEGFA genetic polymorphism as well as VEGF protein levels may be associated with the susceptibility to RA in the Polish population. References: Rodriquez-Rodriquez L et al. Vascular endothelial growth factor A and cardiovascular disease in rheumatoid arthritis patients. Tissue Antigens 2011;77:291-297. Ozgonele L et al. The relation of serum vascular endothelial growth factor level with diseases duration and activity in patients with rheumatoid arthritis. Clin Rheumatol 2010; 29:472-477. Han SW et al. VEGF gene polymorphisms and susceptibility to rheumatoid arthritis. Rheumatology 2004; 43:1173-1177. Zhang Y et al. Vascular endothelial growth factor A (VEGFA) polymorphisms in Chinese patients with rheumatoid arthritis. Scan J Rheumatol 2013; 42: 344-348. Disclosure of Interest: None declared